Evaluation of surface roughness and bond-slip behavior of new textured epoxy-coated reinforcing bars. (30th November 2020) - Zhang, Zige; Jung, Donghyuk; Andrawes, Bassem
Highlights: Comparing surface roughness of six textured epoxy-coated (TEC) reinforcing bars. Utilizing pull-out tests to compare bond-slip of TEC, black and smooth bars. TEC bars have Ra and Rz values 3–4 times that of black bars. TEC bars manifested higher initial slip resistance than black and smooth bars. Adding roughness to epoxy coated bars did not have major impact on bond strength. Abstract: Epoxy-coated reinforcing bars are widely used in bridge decks to mitigate the corrosion of reinforcing steel. Research and practical experience both showed that the smooth epoxy coating significantly reduces the bond between concrete and reinforcing steel, which often results in the early development of transverse cracks in bridge decks. To solve this problem, the Illinois Department of Transportation (IDOT) proposed a new type of textured epoxy-coated (TEC) reinforcing bars with applied roughness to improve the bond between concrete and steel while providing corrosion protection. This study investigates the surface roughness of six different types of TEC bars and how it impacts the bar's bond-slip behavior with concrete. First, the surface roughness of the TEC bars is compared with that of uncoated black bars (BLK) using 2-D parameters Ra, Rz, and 3-D parameters Sa and Sz . Second, direct pull-out tests are conducted on concrete specimens with embedded 1) BLK, 2) smooth epoxy-coated (SEC), and 3) all six TEC bars to compare their bond characteristics. Finally, a 3-D finite element model is developed and calibrated to simulate the bond-slip behavior of TEC bars embedded in concrete. The results show that the average surface roughness of TEC bars is 3–4 times that of the uncoated bars. Further, TEC bars generally exhibit higher slip resistance than the uncoated and smooth epoxy-coated bars.